Alkylsulfonamide-containing quinazoline derivatives as potent and orally bioavailable PI3Ks inhibitors. Issue 20 (15th October 2019) - Hei, Yuan-Yuan; Zhang, San-Qi; Feng, Yifan; Wang, Jin; Duan, Weiming; Zhang, Hao; Mao, Shuai; Sun, Haopeng; Xin, Minhang
Graphical abstract: Highlights: Alkylsulfonamide-containing quinazoline derivatives was synthesized. CompoundA1 displayed potent inhibitory activity against the PI3K. CompoundA1 inhibited HCT-116, MCF-7 and SU-DHL-6 cells growth. A1 markedly inhibit cancer growth in nude mouse HCT-116 xenograft model in vivo . Abstract: Phosphoinositide 3-kinases (PI3Ks) are regarded as promising targets for treatment of various cancers due to their roles in regulating cell proliferation, differentiation, migration, and survival. Here we report our efforts to develop potent and orally bioavailable PI3K inhibitors for the treatment of cancers. The alkylsulfonamide-containing quinazoline derivativesA1–A18 significantly inhibited PI3Kα, and cell proliferation among HCT-116, MCF-7 and SU-DHL-6 cell lines. The optimal compoundA1 displayed potent inhibitory activity against PI3Kα (IC50  = 4.5 nM), PI3Kβ (IC50  = 4.5 nM), PI3Kγ (IC50  = 4.5 nM), PI3Kδ (IC50  = 4.5 nM) and significantly inhibited the growth of HCT-116, MCF-7 and SU-DHL-6 cell lines with IC50 values of 0.82 µM, 0.99 µM and 0.19 µM, respectively. Western blot analysis demonstratedA1 significantly suppressed the phosphorylation of AKT S473 in a dose-dependent manner. Furthermore, A1 could markedly inhibit cancer growth at the dose of 25 mg/kg in nude mouse HCT-116 xenograft model in vivo without causing significant weight loss or toxicity.